Dosis de ceniza de madera y sus efectos en las características agronómicas y rendimiento de Brassica juncea L. "mostaza de hoja", en Zungarococha-Loreto.2022 - Moncada Huancho, Sandro (2023)
The study of leaf mustard with application of doses of wood ash, was consummated in Zungarococha, being its coordinates of 9575237 North and 682257 South. The objective was to study the effects of wood ash on cultivation. The design was that of Complete Random Blocks, concluding that ash significantly influences treatments, where the T4 of 3 t of ash / ha, found excellent effects, with height 39 cm, width 51 cm; root length and weight 22 cm and 14 g, petiole length 19 cm. The best yields of number, leaf/plant weight and plant weight were 17 units, 450 g and 467 g respectively. The best yield/ha of leaf weight and plant weight/ha were 30,000.15 Kg and 31,133,489 Kg. The best economic benefit/ha was S/.21,409.50 and was met with T4.